Nomothetic and Idiographic Strategies for Clinical Research: In Apposition or Opposition? - Ottenbacher, Kenneth (OTJR (Thorofare, N.J.), 1984)
The use of large-N group comparison research strategies based on a nomothetic model is compared and contrasted with idiographic methods employing single-system designs and advocating the intensive study of the individual The limitations of research design and analysis based on a nomothetic model are reviewed, and some corresponding advantages of the idiographic approach are presented A bias has existed in the generation of empirical knowledge in the behavioral and social sciences which favored the use of large-N group comparison designs This bias may result in a research literature with limited clinical relevance for the individual client or consumer of occupational therapy services. The argument is made that both nomothetic and idiographic approaches represent valid methods of establishing the effectiveness of therapeutic interventions. The implications for occupational therapy practice and research are briefly discussed.